Scienza e arte chimica, arti figurative e letteratura - Schettino, Vincenzo (Studi e saggi, 2014)
During the creative act, the artist and the scientist both proceed through the decoding and recomposition of the realities they observe. Based on this method correspondence, art and science offer tools to study the inner or outer reality, looking at objects and situations and looking for correlations and interpretations, in an ideal relationship between the artist's study and the scientist's laboratory . Starting from this unitary vision of the cognitive processes, the interactions between chemistry and decorative arts, between chemistry and architecture and between chemistry and literature (poetry, theater, narrative) are examined, highlighting sometimes unexpected and surprising analogies and overlappings.